Biochemical Alterations in DNA Content of Gill and Gonad Tissues of Corbicula striatella due to 5Ã‚Â¬-Fluorouracil Toxicity - A. V. Andhale2; S. P. Zambare2, P. A. Bhosale1 (Recent Research in Science and Technology, 2011)
Present paper deals with study of impact of 5flurouracil on DNA content of gill and gonad of Corbicula striatella. It was found that DNA content of gill and gonad of Corbicula striatella was decreased due to 5flurouracil afterÃ‚Â Ã‚Â 15 and 30 days.